2007
DOI: 10.1038/nature05724
|View full text |Cite
|
Sign up to set email alerts
|

Image statistics and the perception of surface qualities

Abstract: The world is full of surfaces, and by looking at them we can judge their material qualities. Properties such as colour or glossiness can help us decide whether a pancake is cooked, or a patch of pavement is icy. Most studies of surface appearance have emphasized textureless matte surfaces, but real-world surfaces, which may have gloss and complex mesostructure, are now receiving increased attention. Their appearance results from a complex interplay of illumination, reflectance and surface geometry, which are d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

28
542
5
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 557 publications
(577 citation statements)
references
References 24 publications
28
542
5
2
Order By: Relevance
“…In many cases, proper recovery of many materialrelated physical parameters solely from the available sensory information is computationally difficult. Thus, it has been suggested that the mechanism for material perception heuristically uses simple stimulus features correlated with the physical material properties under a range of natural environments (25,28,29). In agreement with this idea, our present findings indicate that the mechanism for material perception is sensitive to the presence and absence of specific ranges of spatiotemporal frequency components in the image deformation flow.…”
Section: Discussionsupporting
confidence: 81%
“…In many cases, proper recovery of many materialrelated physical parameters solely from the available sensory information is computationally difficult. Thus, it has been suggested that the mechanism for material perception heuristically uses simple stimulus features correlated with the physical material properties under a range of natural environments (25,28,29). In agreement with this idea, our present findings indicate that the mechanism for material perception is sensitive to the presence and absence of specific ranges of spatiotemporal frequency components in the image deformation flow.…”
Section: Discussionsupporting
confidence: 81%
“…Second, the findings illustrate that the visual system might sometimes use simple and unexpected strategies to optimize its solutions to perceptual problems (40,41). In our case, the lightness of the object is better estimated by the brighter regions of the object and oversampling the brighter parts is thus a good heuristic to estimate the lightness of the object.…”
Section: Discussionmentioning
confidence: 79%
“…and whether the visual system extracts information carried by specular highlights~Beck, 1964; Hurlbert et al, 1989;Yang & Maloney, 2001!. Not much is known about the interaction of color appearance and the material from which an object is made; only a few studies examine this question in the more restricted domain of lightness perception~Nishida & Shinya, 1998;Todd et al, 2004;Motoyoshi et al, 2007!. We return to the relation between our work and this literature in the discussion.…”
Section: Introductionmentioning
confidence: 91%